Maqasid al-Shari'ah of zakat towards sustainable economy - Saleh, Abdulmajid Obaid Hasan; Qatawneh, Mohammad Abdelhamid Salem; Saged, Ali Ali Gobaili (Routledge, Taylor & Francis Group, 2024)
Questions arise on the efficiency of zakat collection and distribution and its socioeconomic effects from maqasid al-Shari’ah perspective. This study attempts to expound some anticipated objectives (maqasid) and wisdoms of zakat obligation which is one of the pillars of Islam. In relation to this, there are some current issues pertaining to the collection of zakat, such as the legitimacy of zakat on paper money, commercial crops and fruits and different kinds of incomes and mechanisms to improve zakat collection and distributions. This study proposes some alternatives to resolve those issues from the maqasid perspectives.